Dating Violence Continuity: The Protective Role of Self-Esteem Against Revictimization by Multiple Partners - Hébert, Élizabeth (Journal of interpersonal violence, 2025)
Dating violence is a deleterious relational dynamic that affects around one-third of adolescents. It is well documented that dating violence can persist over time, occurring within the same relationship or across multiple relationships. Self-esteem could be a key factor in understanding the mechanisms of violence continuity, potentially acting as a protective factor during adolescence. Exploring its role in the continuity of dating violence and the potential differences based on whether the violence occurs within the same relationship or across different relationships could inform interventions aimed at preventing repetitive violence and revictimization by multiple partners. This study aimed to (1) examine the association between dating violence measured at two distinct time points, (2) investigate the moderating role of self-esteem in this association, and (3) explore potential variations in the protective role of self-esteem based on whether the violence reoccurred within the same relationship or across different relationships. Sex differences were also examined. A subsample of 1,018 adolescents who reported being involved in a dating relationship at two time points completed self-reported questionnaires. A moderation analysis revealed that dating violence at Time 1 predicted dating violence at Time 2 (6 months later) for both boys and girls. Among girls, self-esteem acted as a protective factor when considering the effect of partner change. Hence, girls who experienced dating violence victimization at Time 1 but had higher self-esteem were more inclined to engage in a subsequent relationship devoid of dating violence at Time 2. However, self-esteem did not emerge as a significant protective factor among boys. Self-esteem appears to be a pivotal factor in promoting engagement in subsequent positive relationships following experiences of dating violence among girls. These findings offer valuable insight that can inform preventive measures and interventions, ultimately contributing to healthier relationship dynamics and improving the well-being of dating violence victims during adolescence.